P5.036 The First Cluster Randomised Trial of a Molecular Chlamydia and Gonorrhoea Point-Of-Care Assay. (13th July 2013) - Natoli, L; Ward, J; Hengel, B; Causer, L M; Badman, S; Tangey, A; Tabrizi, S N; Whiley, D; Donovan, B; Fairley, C
Abstract : Introduction: In many settings, control of sexually transmissible infections (STIs) is compromised by lack of laboratory infrastructure, physical distance from laboratories and loss to follow up of patients. Point-of-care (POC) tests have the potential to provide timely diagnosis, treatment and partner notification, and in turn reduce infection rates. In April 2013, we will implement the first cluster randomised trial of chlamydia and gonorrhoea POC testing in remote Aboriginal communities where STIs are endemic. Methods: The study, called TTANGO (test, treat and go), will measure the effectiveness, cost-effectiveness and cultural and operational acceptability of POC testing for chlamydia and gonorrhoea infections. The study design is a crossover, cluster, randomised controlled trial involving 12 health services in remote Aboriginal communities in Australia. The primary outcome is the percentage of people with persistent chlamydia and gonorrhoea positive tests. The trial runs for 2 years and is a partnership between research, government and community organisations. Results: TTANGO is reaching the conclusion of the preparation phase and has achieved significant steps, including the engagement of remote health services and communities, a comprehensive laboratory and field evaluation to select the ideal assay, development of the first formal training package for chlamydia and gonorrhoea POC testing, and a quality assurance programme. The GeneXpert® CT/NG molecular POC assay was selected for the trial as it showed very high sensitivity and specificity compared to other assays, was easy to use and results were available in approximately 90 minutes. This paper will discuss progress in preparing and implementing TTANGO, the methodology and evaluation. Conclusion: The results of this RCT will provide crucial information to guide sexual health clinical practise in remote Aboriginal communities and other settings internationally. Mathematical modelling and health economic analyses will be used to make the case for large scale implementation of this technology.